2009
DOI: 10.1164/rccm.200904-0557oc
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Enzyme-linked Immunospot for a Rapid Diagnosis of Tuberculosis

Abstract: Rationale: The rapid diagnosis of pulmonary tuberculosis (TB) is difficult when acid fast bacilli (AFB) cannot be detected in sputum smears. Objectives: Following a proof of principle study, we examined in routine clinical practice whether individuals with sputum AFB smearnegative TB can be discriminated from those with latent TB infection by local immunodiagnosis with a Mycobacterium tuberculosis-specific enzyme-linked immunospot (ELISpot) assay. Methods: Subjects suspected of having active TB who were unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 29 publications
10
114
3
3
Order By: Relevance
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 98%
See 1 more Smart Citation
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 98%
“…NPV in patients with active tuberculosis 18 articles satisfied our inclusion criteria for evaluating the NPV; 13 assessed the NPV among confirmed tuberculosis cases [22,26,[34][35][36][37][38][39][40][41][42][43][44] and six assessed the prospective outcome in IGRA-negative individuals after an average of 2 yrs [19-22, 45, 46]. Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used.…”
Section: Specificitymentioning
confidence: 99%
“…New diagnostic approaches are needed that allow for a more targeted identification of patients at risk to develop TB. This may involve modifications of in vitro immunodiagnostic assays such as the use of novel stimulatory antigens [15,164,165], alternative biomarkers other than IFN-c [166][167][168][169][170][171][172], variations in incubation time [173,174], the readout system [9,12,13,175,176] or the clinical specimen instead of blood [177][178][179]. In addition, both for the detection of LTBI with a risk of reactivation and for suspected active TB, a novel approach based on a whole blood transcriptional signature could provide a biomarker system with high discriminative potential [180].…”
Section: Improvements In the Diagnosis Of Ltbi In Transplant Candidatmentioning
confidence: 99%
“…After a systematic literature search and selection, a total of nine studies with 1214 subjects were included in this meta-analysis [15][16][17][18][19][20][21][22][23]. The article selection process used in the present study is summarized in Figure 1.…”
Section: Clinical Characteristics Of Included Studiesmentioning
confidence: 99%
“…There were 357 patients with SNPT and 857 controls. Seven studies performed in Asia [15][16][17][19][20][21][22] and two studies performed in Europe [18,23]. All studies provided the detailed diagnostic criteria for SNPT, including bacteriology, histopathology or clinical diagnosis, which was widely accepted in Flow chart of selection process for eligible articles studies with tuberculosis diagnosis.…”
Section: Clinical Characteristics Of Included Studiesmentioning
confidence: 99%